Literature Study Of The Effect Of Make a Match Learning Model Assisted With Index Card Match (ICM) Media to Improve Cognitive Learning Outcomes In Civics Learning Elementary School Student: Studi Literatur Pengaruh Model Pembelajaran Make A Match Berbantu Media Index Card Match (ICM) Untuk Meningkatkan Hasil Belajar Kognitif Pada Pelajaran Pkn Siswa Sekolah Dasar - Anggilia Putri; Feri Tirtoni (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to find out the reality in the field which shows that there is teaching Civics subjects without using media which can lead to a decrease in student learning outcomes. The research method used is library research using descriptive methods which are expected so that researchers can examine the development of education through data collection carried out based on relevant books, theories and journals as evidence in this study. The results of this study, among others, conclude that the make a match learning model assisted by the index card match media greatly influences student learning outcomes in Civics subjects and can increase student activity in the process of learning activities. It can be concluded that the make a match learning model assisted by index card match media has an influence on student learning outcomes, can increase enthusiasm in learning and can increase student activity in the learning process.